STRESSORS, EFFECTS AND COPING STRATEGIES AMONG TEACHERS IN SECONDARY SCHOOLS IN EDO STATE, NIGERIA - Iyore, Constance (International Journal of Research -GRANTHAALAYAH, 2018)
The study examined stressors, effects and coping strategies among teachers in secondary schools in Esan Central Senatorial District, Edo State, Nigeria. The descriptive survey design was adopted for the study. The proportionate random sampling technique was used to select a total of three hundred and eight (308) teachers representing 50% of the teachers from the entire population of all the six hundred and sixteen (616) public senior secondary school teachers in Esan Central Senatorial Edo State. The research instrument used was a 30–item questionnaire developed by the researcher and titled Stress Assessment Questionnaire (SAQ) for teachers. The content validity of this instrument was ensured by experts in Measurement and Evaluation, Ambrose Alli University Ekpoma. The test-retest method was used to determine the reliability of the instrument. Descriptive statistics such as mean (X) and standard deviation (S.D) was used to analyze the data collected. The result showed that stress is a cankerworm that emanates from work overload, crowded class conditions, poor working conditions, lack of social support and lack of teaching accessories among others. Based on findings, was concluded that stress lessens teachers’ quality of instructional delivery, lowers teachers’ morale, job satisfaction, job performance and increases attrition among teachers. Hence, it was recommended that teachers in Edo State should always endeavour to manage stress by getting emotional support from others such as more experience teachers who could give them directives on how to manage the current challenges they are facing at school.